ìndices de volume plaquetário e risco de doença cardiovascular em participantes do Estudo Longitudinal de Saúde do Adulto - ELSA - BRASIL - Chams Bicalho Maluf (2015)
The greater understanding of the development of atherosclerotic disease, related to pro-inflammatory and pro-thrombotic functions of platelets, has led to new strategies for control disease. In this sense, the indices that evaluate platelet activity are potential markers for cardiovascular disease (CVD). Platelet function correlates with its volume therefore indices which measure the platelet volume are indirect markers of platelet reactivity. The objective of this study was to determine the relationship between platelet volume indices (PVI) with atherosclerosis risk factors and the Framingham risk score (FRS). Baseline data (2008-2010) of 3115 participants enrolled in the Brazilian Longitudinal Study of Adult Health were used. Mean platelet volume (MPV), platelet distribution width (PDW) and platelet large cell ratio (P-LCR) measurements were strictly controlled. Reference intervals for these three parameters in the study population were determined and pre-analytical interfering factors were analyzed as the impact of time on samples collected in EDTA. The cohort was distributed according to risk factors and the general FRS was estimated. Using the following variables: age, sex, systolic blood pressure, total cholesterol, HDL cholesterol, smoking, diabetes, and use of antihypertensive medications. Multiple linear regression analysis was used to estimate the association between PVI and FRS after adjusting for potential confounders, i.e. variables that are not part of the FRS, but can increase CVD risk and may be related to PVI measures. The multiple linear regression analysis showed that MPV, PDW and P-LCR independently correlated (p 0.01) with FRS after adjustment for confounding variables. One unit increase in MPV, PDW, or P-LCR increased the FRS by 0.59%, 0.40%, and 0.08%, respectively. Diabetics had higher (p 0.004) MPV, PDW, and P-LCR, and hypertensive individuals had higher (p 0.045) PDW and P-LCR. Although the adjusted coefficients of determination of the model were small, risk for CVD results from a complex multi interaction of various risk factors, and platelets play a key role in the pathogenesis of atherosclerosis. The results show that increased PVI is independently associated with higher CVD risk based on the FRS, and is statistically associated with diabetes and systolic hypertension. It appears that the relationship of PVI measures with the FRS is mostly due to their association with diabetes and hypertension, which are part of the FRS. Prospective follow up of this population may help to clarify whether PVI is causally related to CVD in patients with and without diabetes and arterial hypertension.